A meta‐analysis of surgical success rates in Congenital stapes fixation and juvenile otosclerosis. (11th May 2015) - Asik, Burak; Binar, Murat; Serdar, Muhittin; Satar, Bulent
Abstract : Objectives: To assess published reports in the literature on surgical success rates in patients with congenital stapes fixation (CSF) and juvenile otosclerosis (JO). Design: Systematic review of the literature and meta‐analysis of published data. Data Sources: PubMed, SAGE, MEDLINE, and Cochrane. Review Methods: A literature search was performed and evaluated based on established criteria. Two independent reviewers (b.a., m.b. ) inspected titles and abstracts of the studies. The full texts of the studies were examined to assess their relevance to the meta‐analysis. An air‐bone gap (ABG) of 0 to 10 dB hearing level was described as success of surgery. Results: A random effects model was used to analyze the data. A total of 27 studies were included in the meta‐analysis, whereas 934 were excluded. The total number of operated ears was 445 (256 ears with JO and 189 ears with CSF). At the time of surgery, the age of the patients ranged from 3 to 18 years. The success rate was 80.2% for JO and 54% for CSF. The overall success rate was 69.9%. The rate of postoperative sensorineural hearing loss was 3.4% for JO and 2.1% for CSF. Conclusions: Overall, stapes surgery in children with JO or CSF has a moderate success rate (69.9%) to provide ABG closure of 10 dB. The success rate for CSF in the setting of ossicular abnormalities is 54%. This meta‐analysis suggests that if JO can be determined before surgery, a higher success rate is possible (80.2%). Level of Evidence: NA Laryngoscope, 126:191–198, 2016